A review on the effects of processing methods on the nutritional composition and antinutritional components of quinoa (chenopodium quinoa) and buckwheat (Fagopyrum esculentum) / Fatin Nadiah Saypol Anwar and Marina Zulkifli - Saypol Anwar, Fatin Nadiah; Zulkifli, Marina (2021)
Quinoa originally from Andean region and buckwheat from China are two pseudocereals gradually making their way into the daily diet of humans due to its numerous health benefits. Both are packed with nutrients such as essential amino acids, proteins, fibre, vitamins and minerals. However, there is a limitation towards its use due to antinutrient components. Examples of antinutrients include phytate, saponin and tannin that affect the ability to absorb the nutrients. Thus, processing methods were executed in order to observe whether it gives positive or negative impacts towards the nutrients and antinutrients content. Processing methods reviewed include heat treatments (cooking, steaming, boiling, roasting, drying), germination and pressure. In this review, results showed that the roasting and germination process increases the content of nutrients while the process of pressure and microwave produces a lower loss of nutrients. For antinutrients, washing and boiling were the best processing technique to lower the antinutrient contents. It appears that the combination of heat and water would be the most effective way to increase the content of nutrients and lower the antinutrients in both seeds. Deeper research regarding these two pseudocereals is highly recommended, particularly in processing methods because it is proven to positively impact both nutrients and antinutrient components. For that reason, the application of quinoa and buckwheat seeds in the food industry can be expected to be industrialized over time, as they are believed to contain all the essential nutrients which can benefit one's health.